A subquadratic algorithm for minimum palindromic factorization - Fici, Gabriele; Gagie, Travis; Kärkkäinen, Juha; Kempa, Dominik (Journal of discrete algorithms (Amsterdam, Netherlands), 2014)
We give an O(nlog⁡n)-time, O(n)-space algorithm for factoring a string into the minimum number of palindromic substrings. That is, given a string S[1..n], in O(nlog⁡n) time our algorithm returns the minimum number of palindromes S1,…,Sℓ such that S=S1⋯Sℓ. We also show that the time complexity is O(n) on average and Ω(nlog⁡n) in the worst case. The last result is based on a characterization of the palindromic structure of Zimin words.